The Detection of Lymph Node Metastasis Metastases Using a Near-Infrared Fluorescent Probe Based on Tumor-Targeted Monoclonal Antibody Antibodies Specific: A Prospective Study in a Nude Mouse Model - Huarui Yang; Yijun Zhang; Chongyuan Zhu; Yi Zhu; Xuelian Song; Xiaohong Chang; Yi Li (Clinical and Experimental Obstetrics & Gynecology)
Background: To identify the metastatic lymph nodes and remove them accurately, the fluorescent surgical navigation ability of the ovarian cancer-specific fluorescent probe COC183B2-800 was assessed to verify the metastatic lymph nodes in the nude mouse model. Methods: The nude mouse model related to lymph node metastases in human ovarian cancer was established using the SKOV3-ip1 cell line. Besides, the COC183B2-800 probe (IRDye800CW Ester conjugated COC183B2 antibody) was fabricated. Moreover, in vivo fluorescence imaging was performed to determine the ability of the COC183B2-800 fluorescent probe to identify metastatic lymph nodes in the nude mouse model. Results: The nude mouse model related to lymph node metastases in human ovarian cancer was successfully established. In vivo fluorescence imaging was performed 30 hours after the injection of the COC183B2-800 fluorescent probe (25 μg) into the animal model, which can achieve specific imaging of metastatic lymph nodes. All metastatic lymph nodes were detected in vivo and in vitro (8/8), and only 1 negative lymph node with reactive enlargement showed a false positive fluorescent signal. Conclusions: The targeted fluorescent probe COC183B2-800 can be employed to identify metastatic lymph nodes in the nude mouse model related to lymph node metastases in human ovarian cancer with high specificity and sensitivity. Targeted fluorescence imaging using COC183B2-800 is expected to become a method to achieve precise lymphadenectomy.